Engaging Community Health Centers to understand their perceptions and interest in longitudinal cohort research on diabetes mellitus in Native Hawaiian communities: Initial insights from the Waimānalo community - Mau, Marjorie K. Leimomi Mala; Baumhofer Merritt, Nicole Kau'i; Werner, Kamuela; Oneha, Mary Frances (Frontiers in Public Health, 2022)
Despite decades of research on diabetes mellitus (DM) and other health disparities affecting Native Hawaiian and Pacific Islander (NHPI) populations, little is known about the disease mechanisms that underlie these health disparities. Ideally, a longitudinal cohort study is one of the best research design tools to examine underlying mechanisms of disease in health disparity conditions such as DM. The study purpose is to understand the perspectives and insights of people (n=29) living in NHPI communities about conducting longitudinal cohort studies aimed at understanding mechanisms of health disparities in NHPI populations. All interviews were audio-recorded, transcribed and de-identified into written transcripts for thematic content analysis. Four major themes emerged: 1) Diabetes and other health disparities is a community priority because these diseases touch nearly everyone; 2) Cohort-type research and its outcomes should extend beyond data collection to include data sharing using a cultural context approach; 3) Cohort-type research can directly benefit everyone, especially youth, through education on new, locally-derived knowledge; 4) A longterm benefit of cohort-type research should be to support "generational change" in the community. In summary, potential "cohort-type research" (a.k.a. longitudinal cohort study designs) was perceived as a worthy endeavor because health disparities, such as DM, affects nearly everyone in the community. Cohort-type research is important to NHPI communities as it holds promise for impacting "generational change" on health and wellbeing through the sharing of new community-derived knowledge.